University class timetable tool - Ang, Wen Jie (2022)

(untitled)
This project is a timetable scheduling project for purpose of generating the timetable automatically. It will provide the students with the concepts, structures, and design of an automated timetabling tool using Genetic Algorithm. University class timetabling is an optimization problem where sets of the class events need to be scheduled into the timeslots available and at the same time, consider the existence of the constraints. Due to its NP level of difficulty, every added constraint into the timetable scheduling will be resulting in the exponential increment of its complexity. To solve this problem, many algorithms or optimizers had been introduced to simplify the problem complexity, as well as find out the optimal solution for the scheduling. Example of the algorithms are genetic algorithm, particle swarm optimization, simulated annealing, and some other heuristic approaches. As there are different kind of constraints in different institutes or universities, different methods need to be defined to obey the constraints. During the pandemic of Covid-19, the timetable structure has changed greatly, significantly the changes of the study mode which is from physical study mode to online or hybrid mode. In this project, the newly constraints related to the study modes in the timetable scheduling will be defined, genetic algorithm will be studied and used to solve the timetabling problem. Then, create a university class timetabling tool with the newly added constraint. In the end of this project, a university class timetable tool will be developed.